2006
DOI: 10.1088/0953-8984/18/40/005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dimerization and spin polarization on the conductance of a molecular wire

Abstract: We have studied the effects of dimerization on the energy levels of a one-dimensional molecular chain attached between two electrodes. Analytic expressions for the change in energies in the presence of a small perturbing external potential have been obtained for the three limiting cases: (a) uniform, (b) partially dimerized and (c) completely dimerized chains. We find that the presence of dimerization enhances the mixing between low-lying energies in the system resulting in a situation conducive to showing neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…This is first envisioned by Aviram and Ratner in 1974 . Since their first theoretical proposal of using organic molecules as a molecular diode, many experiments and theoretical calculations have been conducted to design new molecules with the desired electrical properties. …”
Section: Introductionmentioning
confidence: 99%
“…This is first envisioned by Aviram and Ratner in 1974 . Since their first theoretical proposal of using organic molecules as a molecular diode, many experiments and theoretical calculations have been conducted to design new molecules with the desired electrical properties. …”
Section: Introductionmentioning
confidence: 99%
“…In most of the experiments, the nanoscale material is an organic molecule or a π-conjugated polymer. Many theories too have been developed from empirical to semi-empirical and ab initio level to describe the electrical response functions of the nanomaterials Pati 2004, 2005;Sengupta et al 2006;Dutta et al 2007;Dutta and Pati 2008a, b).…”
Section: Introductionmentioning
confidence: 99%
“…4) has a near linear dependence on δ. This indicates that the Landau-Zener formula which has the form V c (δ) ∝ [∆ charge (δ)] 2 , is not obeyed although previous studies on finite size systems indicated that tunneling occurs between the Landau quasi-degenerate valence and conduction levels [23,24,25], resulting in an exchange of their symmetries. This is because, at the large N limit, the gap at the critical bias goes to zero and the system goes to a completely conducting state.…”
mentioning
confidence: 99%